(untitled) (Advancements in Homeopathic Research, 2022)
Many Homoeopaths or Professors and Lecturers in Homeopathic Medical Colleges and during seminars or conferences parrotically believe and teach to students without going into the root(s) of the matter or subject that cure should follow according to “Hering’s Law Of Cure” which is explained as follows “Cure takes place from within outward, from above downwards, from the most important organs to the less important organs, and symptoms disappear in the reverse order of their appearance (Hering)”. Is it a Law or Rule or an observation? Is it a man made Law or Natural Law or a Rule or an observation? Natural Laws are fundamental facts. Man made laws which in their essence are not laws in the true sense but rules laid down by man for man which can be amended at a later time or date or year. An observation repeatedly observed and always happens, can be considered as law, for eg; NEWTON’S Law of gravity or gravitational. Did Dr. Hering modify Dr. Hahnemann’s observation? Yes. Hering was known as Hahnemann’s famous student and disciple.